Physiotherapists Construction of their Role in Patient Education - Caladine, Lynne (International Journal of Practice-based Learning in Health and Social Care, 2016)
Objective. The purpose of this study was to understand how physiotherapists articulate their role in patient education with a view to generating new perspectives, and informing debate and curriculum development. Methods. Physiotherapists (16) associated with one higher education institution (HEI) participated in the study and represented a spectrum of educational experience from novice to expert. A qualitative, interpretive study was based on semi-structured interviews which were analysed using a thematic approach to the total data set followed by deeper analysis of key themes drawing on the principles of interpretative repertoire. Results. Four themes were identified: identification with the patient educator role; preparation for the patient educator role; constructs of teaching and learning; therapeutic relationship. Patient education was constructed as an integral and extensive component of practice. Constructs of teaching and learning included transmission and empowerment. Conflicting repertoires of collaboration and compliance were identified in the therapeutic relationship theme. Conclusion. The need for physiotherapists (and other healthcare professionals) to be alert to discourses present within their own narrative and that of others was highlighted. It was also seen to be important to be aware of a tension between transmission-based constructs of patient education, a repertoire of compliance and the goal of patient-centred care. Further research could be carried out to determine the relationship between individuals’ discursive construction of teaching and learning and the methods they adopt when educating patients.